Морфология преимагинальных стадий некоторых видов жуков-чернотелок (Coleoptera, Tenebrionidae) фауны Украины - Черней, Л.С. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2006)
Приведены оригинальные данные по морфологии личинок и куколок двух видов

жуков-чернотелок: Uloma culinaris (Linnaeus, 1758), Odocnemis (Heloponotus)

perplexus (Menetries, 1848). Original new data on the morphology of larvae and pupae of
two species of darkling beetles: Uloma culinaris (Linnaeus, 1758),

Odocnemis (Heloponotus) perplexus
(Menetries, 1848), collected in Ukraine, are given.